Perencanaan Sistem Pengolahan Air Limbah Domestik Dari Kegiatan di Musholla Pada PT.X Untuk Kegiatan Penyiraman RTH - Zulfikar, Achmad; Aussie Amalia (Jurnal Serambi Engineering, 2025)
Addressing the problem of increasingly complex urban household waste requires a multi-aspect approach. This study, therefore, aimed to develop a strategy to manage household wastes in the city of Banda Aceh based on five aspects including policy, institutional, funding, community participation, and operational technique aspects. It was conducted using in-depth interviews with garbage experts and a review of national and municipal policy documents. The qualitative data obtained was processed using Nvivo software. The investigation revealed that legal foundation of municipal waste management derived from the national and city level whereas there is no legal basis at provincial and village levels. In the perspective of institutional aspect, lack of management personnel, budget allocation, and coordination among the key stakeholder have contributed to weak institutions. As regards technical operation aspect, it can be further improved by proper sorting of waste, use of temporary disposal sites, swift waste transportation, time management of waste transportation and non-single use material campaign. Therefore, these aspects need to be developed sustainably to achieve the target of 30% waste reduction by 2025.